Peran Kontrol Diri sebagai Prediktor Perilaku Mengemudi Agresif pada Pengemudi Mobil di Jakarta - Patricia Angeline; Retha Arjadi (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2021)
Many things can cause traffic accident, including the driver behaviour. Aggressive drivingbehaviour is associated with the risk of traffic accident. Aggressive driving behaviour usuallypredicted by external factors, such as other driver’s attitude or gesture that could trigger anger.However, aggressive driving behaviour could also be shown in a situation where there is no otherdriver, for example when someone drive with a high speed in an empty traffic. This means, internalfactor, associated with the ability of the drivers to control themselves, can also contribute toaggressive driving behaviour. This study aims to investigate the role of self-control in predictingaggressive driving behaviour in car driver, specifically in Jakarta. The result from linearaggression analysis shows that self-control significantly predicted aggressive driving behaviourin car drivers in Jakarta. The coefficient is negative, showing that higher self-control determineslower aggressive driving behaviour, and lower self-control determines higher aggressive drivingbehaviour. Practical implications, limitations of the study, and recommendation for future studyare discussed.